Transfer pricing reforms in the context of BEPS: challenges remain (Law and Safety, 2024)
The presence of affiliated entities in different countries and the independence of tax systems make it easy to shift profits from jurisdictions with high corporate tax rates to jurisdictions with low rates. Transfer prices and the arm's length principle are used to prevent profit shifting. The article identifies the peculiarities of transfer pricing reform in the context of the BEPS plan, analyses changes to Ukrainian legislation and opportunities for its improvement.The article analyses the amendments to the Tax Code of Ukraine aimed at ensuring the implementation of the BEPS plan. The shortcomings of these amendments are outlined and amendments are proposed to improve the legislation. The author also examines the compliance with the BEPS guiding principle, which provides for the taxation of profits where profit-generating economic activities are carried out and where value is created. It is established that the amendments to the Tax Code of Ukraine do not ensure the implementation of this principle.In addition to the problems of practical implementation of the provisions of legislation, the article identifies conceptual shortcomings of the proposed improvements to the transfer pricing methods, which practically do not ensure the achievement of the set goals. An alternative method of pricing based on the market assessment of value added, which is determined by the sum of the firm’s factor income, wages and profits, is substantiated. Instead of the concept of “transfer price”, the concept of “fair market price” is introduced, which is determined by the sum of value added, depreciation and expenses, representing the added value of all previous stages of the production and/or distribution cycles. The proposed approach excludes the concepts of “affiliated entities”, “transfer prices” and “arm’s length principle”. The existence of a unified system of value added tax in the European Union allows for the unification of the tax system in terms of direct and indirect taxes as a result of the introduction of fair market prices.Amendments to the legislation have been proposed to allow for automatic solution of the following tasks.
Keywords: affiliated entities; arm’s length principle; business purpose; added value; fair market price.